2017
DOI: 10.1371/journal.pone.0187068
|View full text |Cite
|
Sign up to set email alerts
|

Differential adipokine receptor expression on circulating leukocyte subsets in lean and obese children

Abstract: BackgroundChildhood obesity prevalence has increased worldwide and is an important risk factor for type 2 diabetes (T2D) and cardiovascular disease (CVD). The production of inflammatory adipokines by obese adipose tissue contributes to the development of T2D and CVD. While levels of circulating adipokines such as adiponectin and leptin have been established in obese children and adults, the expression of adiponectin and leptin receptors on circulating immune cells can modulate adipokine signalling, but has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
15
0
5
Order By: Relevance
“…In line with the findings on leptin, adiponectin failed to enhance NK cell activity in obese humans (99). Moreover, studies on obese individuals showed that the expression of the adiponectin receptor 2 is reduced and that low plasma adiponectin concentrations correlated with a diminished cytolytic activity of NK cells from obese individuals (70,81). Taken together, data on adiponectin effects on NK cells are conflicting.…”
Section: Expression Of Granule Componentsmentioning
confidence: 88%
See 1 more Smart Citation
“…In line with the findings on leptin, adiponectin failed to enhance NK cell activity in obese humans (99). Moreover, studies on obese individuals showed that the expression of the adiponectin receptor 2 is reduced and that low plasma adiponectin concentrations correlated with a diminished cytolytic activity of NK cells from obese individuals (70,81). Taken together, data on adiponectin effects on NK cells are conflicting.…”
Section: Expression Of Granule Componentsmentioning
confidence: 88%
“…Investigations demonstrated that the leptin receptor (obesity receptor, ObR) is expressed on splenic and peripheral blood NK cells of rats as well as on human hepatic and peripheral blood NK cells (67-76) ( Table 1). Although leptin receptor expression levels on NK cells are rather dim, functional data upon leptin treatment performed by different laboratories demonstrate a functional role for this receptor on NK cells (69)(70)(71)(72)(73)77).…”
Section: Studies On Leptinmentioning
confidence: 99%
“…Eine Adipokin-vermittelte direkte Regulation von Immunzellen wird durch das Exprimieren der Adipokinrezeptoren vermutet und bietet eine Erklärung für die veränderte Anzahl und Funktion verschiedener Immunzellen durch erhöhte Adipokin-Konzentrationen im Falle einer Adipositas [9,16,[31][32][33]. Monozyten zeigen extrem hohe Oberflächenexpressionsmuster für die Rezeptoren diverser Adipokine [34]. Zudem weisen T-Zellen und NK-Zellen Subpopulations-assoziiert unterschiedliche Adipokin-Rezeptorprofile auf [16,31].…”
Section: Das Adipöse Milieu Verändert Natürliche Killerzellenunclassified
“…The two cytokines that play this role in professional APC, IL‐12 and IL‐18, do not seem to be secreted by adipocytes in significant amounts, suggesting that other factors like adipokines may fulfil this role. Interesting candidates for this are for example leptin and adiponectin, as iNKT cells express the receptors for both adipokines . As leptin levels increase and adiponectin levels decrease in obesity, these adipokines may present an apoptotic/toxic and a pro‐survival signal for iNKT cells, respectively, thereby contributing to the decrease in AT‐resident iNKT cell numbers in obesity.…”
Section: Adipocyte–inkt Cell Interplay: Future Directionsmentioning
confidence: 99%
“…Interesting candidates for this are for example leptin and adiponectin, as iNKT cells express the receptors for both adipokines. 87,88 As leptin levels increase and adiponectin levels decrease in obesity, these adipokines may present an apoptotic/toxic and a pro-survival signal for iNKT cells, respectively, thereby contributing to the decrease in AT-resident iNKT cell numbers in obesity. The finding that Ob/Ob micewhich lack the leptin genedisplay reduced iNKT cell numbers 35 supports this view.…”
Section: Cd1d Loading and Presentationmentioning
confidence: 99%